Adaptation of the Cuban version of the Coronavirus Anxiety Scale - Broche Pérez, Yunier; Fernández Castillo, Evelyn; Fernández-Fleites, Zoylen; Jiménez Puig, Elizabeth; Vizcaíno Escobar, Annia Esther; Ferrer Lozano, Dunia Mercedes; Martínez-Rodríguez, Lesnay; Martín González, Reinier (Taylor & Francis, 2020)
This study explores the psychometric properties of the Cuban version of Coronavirus Anxiety Scale (CAS). The sample comprised 376 Cuban participants. Concurrent validity and reliability were examined. A confirmatory factor analysis was performed. The CAS showed excellent psychometric characteristics. The internal consistency was very good (α = 0.88). There was a positive correlation between the CAS and the FCV-19S and an inverse association between anxiety and self-perceived quality of health. The results confirmed the presence of a single factor. The CAS is a valid and reliable instrument to explore the experience of anxiety in the Cuban population.
Keywords: Anxiety; Psychometrics; COVID-19